Hydration mechanisms of two polymorphs of synthetic ye'elimite - Cuesta-García, Ana María; Álvarez-Pinazo, Gema; Sanfeliz-Garcia, Susana; Peral, Inma; García-Aranda, Miguel Ángel; Gómez-de-la-Torre, María de los Ángeles (Elsevier, 2014)
Ye'elimite is the main phase in calcium sulfoaluminate cements and also a key phase in sulfobelite cements. However, its hydrationmechanismis not well understood. Here we reported newdata on the hydration behavior of ye'elimite using synchrotron and laboratory powder diffraction coupled to the Rietveld methodology. Both internal and external standard methodologies have been used to determine the overall amorphous contents. We have addressed the standard variables: water-to-ye'elimite ratio and additional sulfate sources of different solubilities. Moreover, we report a deep study of the role of the polymorphism of pure ye'elimites. The hydration behavior of orthorhombic stoichiometric and pseudo-cubic solid-solution ye'elimites is discussed. In the absence of additional sulfate sources, stoichiometric-ye'elimite reacts slower than solid-solution-ye'elimite, and AFm-type phases are the main hydrated crystalline phases, as expected. Moreover, solid-solution-ye'elimite produces higher amounts of ettringite than stoichiometric-ye'elimite. However, in the presence of additional sulfates, stoichiometric-ye'elimite reacts faster than solid-solution-ye'elimite.
Keywords: Cemento; Hydration mechanism; Rietveld method; Dissolution and crystallization kinetics; Calcium sulfoaluminate; Ye'elimite